2023
DOI: 10.3390/coatings13091535
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ni-B/B Composite Coatings Produced by Chemical Reduction

Anna Gajewska-Midziałek,
Grzegorz Cieślak,
Marta Gostomska
et al.

Abstract: The paper presents the results of research on composite Ni-B coatings with embedded particles of boron produced by a chemical reduction method and their influence on the mechanical, tribological, and corrosion properties of produced materials. Boron was used in two forms: an alloy component and nanoparticles incorporated into the Ni-B matrix. The coatings were deposited from a bath at different concentrations of dispersion phase. The paper also presents the characteristics of the used boron particles. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Boron in the coating exists in two forms: as a component of the alloyed Ni-B matrix and as a particulate dispersion phase that is incorporated into it. The team's previous work [9] on this type of coatings was carried out on a laboratory scale in beakers (0.5-2 dm 3 ), and their main goal was to determine the conditions for proving the deposition process and the concentration of the dispersion phase (boron) in the electro- To date, research on Ni-B alloy coatings produced electroless has involved laboratoryscale tests in beakers and vessels with capacities ranging from a few hundred cm 3 to a few dm 3 . However, there is a lack of information in the literature on the production of this type of material on an engineering scale in industrial, i.e., close to real, conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron in the coating exists in two forms: as a component of the alloyed Ni-B matrix and as a particulate dispersion phase that is incorporated into it. The team's previous work [9] on this type of coatings was carried out on a laboratory scale in beakers (0.5-2 dm 3 ), and their main goal was to determine the conditions for proving the deposition process and the concentration of the dispersion phase (boron) in the electro- To date, research on Ni-B alloy coatings produced electroless has involved laboratoryscale tests in beakers and vessels with capacities ranging from a few hundred cm 3 to a few dm 3 . However, there is a lack of information in the literature on the production of this type of material on an engineering scale in industrial, i.e., close to real, conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Boron in the coating exists in two forms: as a component of the alloyed Ni-B matrix and as a particulate dispersion phase that is incorporated into it. The team's previous work [9] on this type of coatings was carried out on a laboratory scale in beakers (0.5-2 dm 3 ), and their main goal was to determine the conditions for proving the deposition process and the concentration of the dispersion phase (boron) in the electrolyte at which the properties of the coatings are best. Laboratory tests showed that for a given type of coatings, the most beneficial tribological, mechanical and corrosion properties were obtained for coatings deposited from baths containing 1 g/dm 3 of boron powder as the dispersion phase (TRL 4).…”
Section: Introductionmentioning
confidence: 99%